Adaptive multimode precoding for ultra-broadband vectored DSL systems - Ng, Yin Hoe; Chuah, Teong Chee; Abidin, Ahmadun Nijar Zainal; Hashim, Nabihah; Asrokin, Azhari (Physical communication, 2020)
In the downstream of a digital subscriber line (DSL) system transmitting over a large bandwidth, the row-wise diagonally dominant (RWDD) characteristic of the copper channel matrix, which holds at low frequencies, may not be valid at high frequencies because of the presence of strong crosstalk. Consequently, linear precoders result in sub-optimal bit-rate performance whilst the optimal non-linear precoders incur high computational complexity. In this work, we investigate a quad-mode precoder (QMP) which selectively operates on one of four modes on each frequency tone. A block-based adaptation strategy is introduced for complexity reduction whereby mode selection is invoked adaptively over blocks of tones. The computational complexity associated with the proposed precoder is analyzed and quantified against existing precoders. Results demonstrate that by suitably adapting the operating mode and block length of the proposed QMP according to the channel conditions, moderate computational saving could be attained without compromising the bit-rate performance. More importantly, the QMP facilitates green DSL as energy savings are feasible when some tones are de-activated to conserve energy.